Global, national and local frameworks: tourism, cultural politics and contested place identity - Muhvić-Dimanovski, Vesna; Sujoldžić, Anita; Orlić, Olga; Bertoša, Mislava (2010)
In recent years both tourism promotion and various other activities in the tourism sector have been operating between global, national and local frameworks. More and more countries are making strenuous efforts to present themselves as desirable destinations for foreign visitors. In order to be visible on the global market, these countries undertake various promotional activities to represent their cultural heritage by drawing not only on the pre-existent resources, but also on the public discourses implemented in creating and maintaining the national identity. On the other hand within the context of globalisation, regional cultures are increasingly pressured to become more important in making a distinctive offer to the tourist markets. At the same ti me, in a broader context both regions and countries strive to demonstrate their ‘Europeanness’ and to comply with the UNESCO policies on tourism and cultural heritage. These four levels (being in constant interrelation) have a great impact on place identities, the lives of the local population and the perception of tourists. This paper addresses the impact of the interplay of these different strategies and discourses on tourism and the construction of place identity in the multi cultural Croatian region of Istria and its major city of Pula. The complex relations of various factors – both from the point of view of the locals and those who are engaged in tourism business at various levels – lead to new perspectives of tourist destinations as being places that integrate the global and the local. Places – like people – can have multiple identities which can be a source of richness but also of conflict. The findings indicate that selections of what to present through idealized touristic images, constructed as official representations or regimes of truth often conceal contestations of cultural values and heritage traditions, and that tourism should be approached as a political and ideological field of struggle that has important repercussions on identity and local cultures.
Projekt MZOS
ENG